Freshwater Algae of North America : Ecology and Classification. - Wehr, John D. (Aquatic Ecology., 2015)
Freshwater Algae of North America: Ecology and Classification, Second Edition is an authoritative and practical treatise on the classification, biodiversity, and ecology of all known genera of freshwater algae from North America. The book provides essential taxonomic and ecological information about one of the most diverse and ubiquitous groups of organisms on earth. This single volume brings together experts on all the groups of algae that occur in fresh waters (also soils, snow, and extreme inland environments). In the decade since the first edition, there has been an explosion of new information on the classification, ecology, and biogeography of many groups of algae, with the use of molecular techniques and renewed interest in biological diversity. Accordingly, this new edition covers updated classification information of most algal groups and the reassignment of many genera and species, as well as new research on harmful algal blooms. Extensive and completeDescribes every genus of freshwater algae known from North America, with an analytical dichotomous key, descriptions of diagnostic features, and at least one image of every genus. Full-color images throughout provide superb visual examples of freshwater algaeUpdated Environmental Issues and Classifications, including new information on harmful algal blooms (HAB)Fully revised introductory chapters, including new topics on biodiversity, and taste and odor problemsUpdated to reflect the rapid advances in algal classification and taxonomy due to the widespread use of DNA technologies.